Predictive Factors of Neurological Complications and One-Month Mortality after Liver Transplantation - Fu, Katherine A.; DiNorcia, Joseph; Sher, Linda; Velani, Shamsha A.; Akhtar, Shahrzad; Kalayjian, Laura A.; Sanossian, Nerses (Frontiers in Neurology, 2014)
Background: Neurological complications are common after orthotopic liver transplantation (OLT). We aimed to characterize the risk factors associated with neurological complications and mortality among patients who underwent OLT in the post-model for end-stage liver disease (MELD) era. Methods: In a retrospective review, we evaluated 227 consecutive patients at the Keck Hospital of the University of Southern California before and after OLT to define the type and frequency of and risk factors for neurological complications and mortality. Results: Neurological complications were common (n = 98), with encephalopathy being most frequent (56.8%), followed by tremor (26.5%), hallucinations (11.2%), and seizure (8.2%). Factors associated with neurological complications after OLT included preoperative dialysis, hepatorenal syndrome, renal insufficiency, intra-operative dialysis, preoperative encephalopathy, preoperative mechanical ventilation, and infection. Preoperative infection was an independent predictor of neurological complications (OR 2.83, 1.47–5.44). One-month mortality was 8.8% and was independently associated with urgent re-transplant, preoperative intubation, and intra-operative arrhythmia. Conclusion: Neurological complications are common in patients undergoing OLT in the post-MELD era, with encephalopathy being most frequent. An improved understanding of the risk factors related to both neurological complications and one-month mortality post-transplantation can better guide perioperative care and help improve outcomes among OLT patients.